Recovering bodies : illness, disability, and life-writing - Couser, G. Thomas (Wisconsin studies in American autobiography., 1997)
"A compelling look at personal narratives of HIV/AIDS, breast cancer paralysis, and deafness, Recovering Bodies examines many forms of life writing - including memoirs, diaries, collaborative narratives, photo documentaries, and essays - to illuminate the ways in which these narratives address the stigma of illness and disability. G. Thomas Couser shows that such books are not primarily records of medical conditions; they are instead a means for individuals to reclaim their bodies (or those of loved ones) from marginalization and impersonal medical discourse, by telling their stories in their own terms." "Couser considers why and under what circumstances individuals choose to write about illness or disability; what role plot plays in such narratives; how closure is achieved; who assumes the prerogative of narration; which conditions are most often represented; and which literary conventions lend themselves to representing particular conditions. By tracing the development of new subgenres of personal narrative in our time, this book explores how explicit consideration of illness and disability has enriched the repertoire of life writing. In addition, Couser's discussion of medical discourse joins the current debate about whether the biomedical model is entirely conducive to humane care for ill and disabled people." "With its sympathetic critique of the testimony of those most affected by these conditions, Recovering Bodies contributes to an understanding of the relations among bodily dysfunction, cultural conventions, and identity in contemporary America."--Jacket.